2016
DOI: 10.3389/fpls.2016.00219
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of ICP-Detected Nutrient Accumulation in the Whole Seed of Common Bean (Phaseolus vulgaris L.)

Abstract: Nutrient transport to grain legume seeds is not well studied and can benefit from modern methods of elemental analysis including spectroscopic techniques. Some cations such as potassium (K) and magnesium (Mg) are needed for plant physiological purposes. Meanwhile, some minerals such as copper (Cu), iron (Fe), molybdenum (Mo), and zinc (Zn) are important micronutrients. Phosphorus (P) is rich in legumes, while sulfur (S) concentration is related to essential amino acids. In this research, the goal was to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 66 publications
(89 reference statements)
3
24
0
Order By: Relevance
“…However, the assisted selection with molecular markers can be a viable alternative to the biofortification programs in common beans. Recent studies revealed the discovery of two quantitative trait loci (QTL) associated with the potassium concentration in a recombinant inbred line of common bean (F 9:11 generation), one QTL was found for calcium, and three QTL´s were found for magnesium (Blair et al, 2016).…”
Section: Genetic Variability and Genetic Parameters For The Macrominementioning
confidence: 99%
“…However, the assisted selection with molecular markers can be a viable alternative to the biofortification programs in common beans. Recent studies revealed the discovery of two quantitative trait loci (QTL) associated with the potassium concentration in a recombinant inbred line of common bean (F 9:11 generation), one QTL was found for calcium, and three QTL´s were found for magnesium (Blair et al, 2016).…”
Section: Genetic Variability and Genetic Parameters For The Macrominementioning
confidence: 99%
“…An essential element is an element that if absent or removed from the diet or intake can cause a consistent and reproducible misfunctioning of a physiological process in an organism [19]. Bone development in human beings are requires Ca and if taken in sufficient amount can prevent fractures and bone malformations [20,21]. In the same way, K and Na are required for nerve impulses and ion transport through membranes of tissues; P and Mg are required by the cells for the production of ATP [21,22].…”
Section: Icp-msmentioning
confidence: 99%
“…Bone development in human beings are requires Ca and if taken in sufficient amount can prevent fractures and bone malformations [20,21]. In the same way, K and Na are required for nerve impulses and ion transport through membranes of tissues; P and Mg are required by the cells for the production of ATP [21,22]. On the contrary, excessive intakes of these minerals can result in toxicity though most minerals have a fairly wide range of adequate intake making deficiency or toxicity relatively rare if proper diets are taken.…”
Section: Icp-msmentioning
confidence: 99%
See 1 more Smart Citation
“…The biggest producers are Brazil, USA and Mexico, while millions of tons are produced annually in Africa. Its high levels of protein and carbohydrate make common bean a staple in food, and it is an important source of vitamins and minerals, including iron, magnesium, potassium, zinc, selenium and calcium [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%